ChemInform Abstract: A Highly Facile Approach to the Synthesis of Novel 2‐(3‐Benzyl‐2, 4‐dioxo‐1, 2, 3, 4‐tetrahydropyrimidin‐1‐yl) ‐N‐phenylacetamides. Issue 22 (13th May 2013) - Novikov, Mikhail S.; Babkov, Denis A.; Paramonova, Maria P.; Chizhov, Alexander O.; Khandazhinskaya, Anastasia L.; Seley‐Radtke, Katherine L.
Abstract A facile and high‐yielding procedure for the preparation of N‐arylacetamides (IV) via N‐silylation is developed which avoids intractable work‐up and by‐products.